Analysis of some data of infectious and parasitic diseases in the context of planned changes in the health system of Republic of Crimea - A. L. Pavlenko; S. V. Kozulya (Кубанский научный медицинский вестник)
Russian Federation and Ukraine have various regulatory legal acts governing the registration of infectious and parasitic diseases and epidemiological surveillance in general. Due to adoption of the health standards of Russian Federation in Republic of Crimea in 2015, we can expect the increase of infectious and parasitic diseases in some nosology. But this process cannot be associated with worsening the epidemiological situation in Crimea; it may be the result of improving the quality of clinical, laboratory and epidemiological diagnosis. Accession the new region to the Russian Federation and the associated change in the health care system can provide valuable information that compares performance of selected elements of the two systems and use the data to improve them.